A critical role of hepatitis B virus polymerase in cirrhosis, hepatocellular carcinoma, and steatosis. Issue 1 (19th December 2017) - Chung, Hea‐Jong; Chen, Xiao; Yu, Yang; Lee, Heui‐Kwan; Song, Chang Ho; Choe, Han; Lee, Seungkoo; Kim, Hyeon‐Jin; Hong, Seong‐Tshool
Abstract : Hepatitis B is one of the most common infectious diseases in the world; more than 350 million people are carriers of hepatitis B virus (HBV). Chronic HBV infection (CHB) leads to liver diseases such as cirrhosis, hepatocellular carcinoma (HCC), and steatosis. Despite its seriousness in terms of public health, the pathogenic mechanism of how CHB leads to liver diseases, especially cirrhosis and steatosis, remains unclear. We studied the role of HBV polymerase (HBp) reverse transcriptase (RT) activity in association with the pathogenesis of liver diseases in CHB by developing transgenic mice expressing HBp or the RT domain of HBp. Thorough pathological, serological, and histological analyses of the transgenic mice, as well as mechanistic studies, were conducted. All of the transgenic mice expressing RT in their livers developed early cirrhosis with steatosis by 18 months of age, and 10% developed HCC. The RT activity of HBp stimulates coordinated proapoptotic and proinflammatory responses involving the caspase‐9, caspase‐3, and caspase‐1 pathways that might lead to the development of cirrhosis, HCC, and steatosis. The animal model described here should prove useful for elucidating the molecular events in the CHB‐induced liver diseases. Abstract : Chronic hepatitis B virus (CHB) infection leads to liver diseases such as cirrhosis, hepatocellular carcinoma (HCC), and steatosis. We developed transgenic mice expressing HBV polymerase (HBp) or its reverse transcriptase (RT) domain to study the role of this viral enzyme in the pathogenesis of liver diseases. Transgenic mice expressing RT in their livers developed early cirrhosis and steatosis, and 10% developed HCC. We also showed that HBp RT activity stimulates proapoptotic and proinflammatory responses that might lead to the development of cirrhosis, HCC, and steatosis.